Peningkatan Status Kesehatan dan Gizi Anak Melalui Edukasi 1000 Hari Pertama Kehidupan di Desa Tanggobu - Fadmi, Fitri Rachmillah; Mulyani, Sri; Syaban, Quriatul (Abdimas Universal, 2026)
Nutritional problems remain a major public health concern in Indonesia, particularly in developing regions such as Southeast Sulawesi Province. According to the 2025 Health Profile, the prevalence of stunting in this province is still around 27 to 30 percent. This situation indicates that public awareness regarding proper nutrition from pregnancy until the first two years of a child’s life still needs to be strengthened. This community service program was implemented in Tanggobu Village, Morosi Subdistrict, Konawe Regency an active mining area with socioeconomic challenges that can affect child care and nutritional fulfillment. The main goal of this activity was to improve the health and nutritional status of children through education on the importance of the First 1000 Days of Life (1000 HPK) as a preventive effort against stunting. The activity involved 35 mothers of toddlers and was carried out through interactive lectures and group discussions. Participants’ knowledge was measured before and after the educational intervention to assess its effectiveness.The results showed an increase in the average knowledge score from 4.91 to 7.69 with a p < 0.05, indicating a significant difference after the educational session. This improvement demonstrates that educational interventions effectively enhanced mothers’ understanding of balanced nutrition and proper childcare practices. It is recommended that similar programs be conducted regularly and integrated with community health services to encourage sustainable behavioral changes toward healthier and more nutritious families.